2015
DOI: 10.15537/smj.2015.11.12891
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation cardioversion following acupuncture

Abstract: Atrial fibrillation (AF) is the most common arrhythmia and it is an independent risk for serious events. Acupuncture has been growing in popularity in the West, and there are reports of its benefits in treating AF. We report a 57-year-old man who was admitted after having an allergic reaction to amiodarone administered to treat paroxysmal AF with fast ventricular response. Cardioversion with intravenous propafenone was uneventful. Before an attempt of electric cardioversion, he was treated with acupuncture as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Dilber et al showed that when a 57 years old patient with paroxysmal AF was treated with acupuncture after other methods failed to convert AF, it successfully converted AF to sinus rhythm. During 30 days follow up, there was no AF recurrence in the patients after sinus rhythm was established by acupuncture combined with peroral propafenone [20]. These experiments illustrated that acupuncture was effective in treating AF patients, but they were not completely randomised controlled trials (RCTs), and the cases of AF were few.…”
Section: Discussionmentioning
confidence: 99%
“…Dilber et al showed that when a 57 years old patient with paroxysmal AF was treated with acupuncture after other methods failed to convert AF, it successfully converted AF to sinus rhythm. During 30 days follow up, there was no AF recurrence in the patients after sinus rhythm was established by acupuncture combined with peroral propafenone [20]. These experiments illustrated that acupuncture was effective in treating AF patients, but they were not completely randomised controlled trials (RCTs), and the cases of AF were few.…”
Section: Discussionmentioning
confidence: 99%
“…Lifting and thrusting Dilber et al [34] Filiform needle acupuncture Zusanli, Shenmen, and Neiguan Patients with paroxysmal atrial fibrillation…”
Section: Minmentioning
confidence: 99%
“…Acupoint selection focuses on the interaction between the circulation of meridians and the use of specific acupoints. The main acupoints for AF are Neiguan (PC6), Qihai (RN6), Zhongwan (RN12) and Danzhong (RN17) points, and the highest selection frequency acupoint is Neiguan (PC6) point [18][19][25][26][27][28][29][30][31][32][33][34] (Table 1). Neiguan (PC6) point, as the collateral point of the pericardium meridian, is frequently used to regulate qi and blood in the heart, and the core prescriptions of acupoint compatibility are Danzhong (RN17), Xinshu (BL15) and Neiguan (PC6) points [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture and AF Published data also shows that "acupuncture treatment prevents arrhythmic recurrences after cardioversion in patients with persistent AF. This minimally invasive procedure is safe and well tolerated" (10,11,12,13), Integrated (serial) acupuncture treatments have resulted in AF cessation.…”
Section: Glycogen and Afmentioning
confidence: 99%